A conceptual model of the controlling factors of soil organic carbon and nitrogen densities in a permafrost‐affected region on the eastern Qinghai‐Tibetan Plateau. Issue 7 (20th July 2017) - Wu, Xiaodong; Fang, Hongbing; Zhao, Yonghua; Smoak, Joseph M.; Li, Wangping; Shi, Wei; Sheng, Yu; Zhao, Lin; Ding, Yongjian
Abstract: Many investigations of the preservation of soil organic carbon (SOC) in permafrost regions have examined roles of geomorphology, pedogenesis, vegetation cover, and permafrost within particular regions. However, it is difficult to disentangle the effects of multiple factors on the SOC in permafrost regions due to the heterogeneity in environmental conditions. Based on data from 73 soil study sites in permafrost regions of the eastern Qinghai‐Tibetan Plateau, we developed a simple conceptual model, which relates SOC to topography, vegetation, and pedogenesis. We summarized the dominant factors and their controls on SOC using 31 measured soil physiochemical variables. Soil texture explains approximately 60% of the variations in the SOC stocks for the upper 0–2 m soil. Soil particle size closely correlates to soil moisture, which is an important determinant of SOC. Soil salinity and cations are important factors as well and can explain about 10% of the variations in SOC. The SOC and total nitrogen (TN) stocks for the 1–2 m depths have larger uncertainties than those of upper 1 m soil layer. The vegetation, pH, and bulk density mainly affects SOC and TN stocks for the upper 1 m soil layers, while the active layer thickness and soil particle size have greater influence on SOC and TN stocks for the 1–2 m soils. Our results suggest that the soil particle size is the most important controller of SOC pools, and the stocks of SOC and TN are strongly effected by soil development processes in the permafrost regions of the eastern Qinghai‐Tibetan Plateau. Key Points: Soil texture is the most important determinant of organic carbon and total nitrogen content Vegetation, pH, and bulk density are major controllers of C and N at 0–1 m; permafrost and soil texture have greater influence at 1–2 m A conceptual model was developed to describe the environmental controllers of soil organic carbon Plain Language Summary: Soil organic carbon in permafrost regions is important to global warming. There are many factors that can affect soil organic carbon content in permafrost regions. How to describe the contributions of these factors to organic carbon? Are there any relationship between these factors? Here we analyzed the multiple factors which related to soil organic carbon and proposed a conceptual model to present the complex interactions between soil carbon and environmental factors. Our results showed that finer soil particles contributed the largest proportions of soil organic carbon in permafrost regions.